2016
DOI: 10.3758/s13428-016-0714-4
|View full text |Cite
|
Sign up to set email alerts
|

Confidence intervals for single-case effect size measures based on randomization test inversion

Abstract: In the current paper, we present a method to construct nonparametric confidence intervals (CIs) for single-case effect size measures in the context of various single-case designs. We use the relationship between a two-sided statistical hypothesis test at significance level α and a 100 (1 -α) % two-sided CI to construct CIs for any effect size measure θ that contain all point null hypothesis θ values that cannot be rejected by the hypothesis test at significance level α. This method of hypothesis test inversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 73 publications
0
29
0
Order By: Relevance
“…Statistical inference refers to assessing the statistical significance of treatment effects through hypothesis testing or by constructing confidence intervals for the parameter estimates (Heyvaert et al, 2015;Michiels, Heyvaert, Meulders, & Onghena, 2017). On the one hand, inferential procedures can be divided into parametric and nonparametric procedures, and on the other hand, they can be divided into frequentist and Bayesian procedures.…”
Section: Data Analysis Of Randomized Ab Phase Designs: Techniques Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical inference refers to assessing the statistical significance of treatment effects through hypothesis testing or by constructing confidence intervals for the parameter estimates (Heyvaert et al, 2015;Michiels, Heyvaert, Meulders, & Onghena, 2017). On the one hand, inferential procedures can be divided into parametric and nonparametric procedures, and on the other hand, they can be divided into frequentist and Bayesian procedures.…”
Section: Data Analysis Of Randomized Ab Phase Designs: Techniques Andmentioning
confidence: 99%
“…When measurement occasions are randomized to treatment conditions according to the employed randomization scheme, a statistical reference distribution for a test statistic S can be calculated. This reference distribution can be used for calculating nonparametric p values or for constructing nonparametric confidence intervals for S by inverting the RT (Michiels et al, 2017). The RT is also flexible with regard to the choice of the test statistic (Ferron & Sentovich, 2002;Onghena, 1992;Onghena & Edgington, 2005).…”
Section: Data Analysis Of Randomized Ab Phase Designs: Techniques Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical inference refers to determining the statistical significance of ES measures through statistical hypothesis testing or to constructing confidence intervals for parameter estimates (Heyvaert et al, 2015;Michiels, Heyvaert, Meulders & Onghena, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Both are equivalent in the sense that for a certain test statistic θ, the 100(1 -α)% twosided confidence interval contains all point null values of θ that cannot be rejected by a two-sided hypothesis test at significance level α. HTI can be used with either parametric hypothesis tests or nonparametric hypothesis tests such as RTs. Michiels, Heyvaert, Meulders, and Onghena (2017) already showed that nonparametric confidence intervals for single-case ESs can be constructed from the RT using HTI.…”
Section: Constructing Confidence Intervals For Combined Effect Sizesmentioning
confidence: 99%